2014
DOI: 10.1103/physrevb.90.195426
|View full text |Cite
|
Sign up to set email alerts
|

Large conduction band and Fermi velocity spin splitting due to Coulomb interactions in single-layerMoS2

Abstract: We study the effect of Coulomb interactions on the low energy band structure of single-layer transition metal dichalcogenide semiconductors using an effective low energy model. We show how a large conduction band spin splitting and a spin dependent Fermi velocity are generated in MoS2, as a consequence of the difference between the gaps of the two spin projections induced by the spinorbit interaction. The conduction band and Fermi velocity spin splittings found are in agreement with the optical absorption ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Furthermore, detailed magneto-transmission experiments have revealed that the reduced mass of the exciton in monolayer MoS 2 is heavier than predicted by density functional theories [28,34], suggesting a large electron mass consistent with recent values determined from transport studies of n-type MoS 2 monolayers [35]. The complicated interplay of band structure [28,36], electron-electron interactions [11,24,37,38], enhanced spin-splitting [39], dynamical effects [40] and inter-/ intra-valley phonon [41] and plasmon [20] contributions makes MoS 2 one of the most challenging materials to understand.…”
Section: Introductionsupporting
confidence: 72%
“…Furthermore, detailed magneto-transmission experiments have revealed that the reduced mass of the exciton in monolayer MoS 2 is heavier than predicted by density functional theories [28,34], suggesting a large electron mass consistent with recent values determined from transport studies of n-type MoS 2 monolayers [35]. The complicated interplay of band structure [28,36], electron-electron interactions [11,24,37,38], enhanced spin-splitting [39], dynamical effects [40] and inter-/ intra-valley phonon [41] and plasmon [20] contributions makes MoS 2 one of the most challenging materials to understand.…”
Section: Introductionsupporting
confidence: 72%
“…The calculation of µ and of ∂µ/∂n is carried out by performing numerically the first and the second derivatives, respectively, of the ground-state energy, which, in turn, are known only numerically from Eqs. ( 13) and (19).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The magnetic properties of MoS 2 nanoribbons indicate that the electron-electron interactions are not negligible. Furthermore, the effect of Coulomb interactions on the low-energy band structure of MoS 2 using an effective two-band model Hamiltonian has been recently studied [19] and the study showed that a large conduction band spin splitting and a spin dependent Fermi velocity are generated due to the Coulomb interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent photoluminescence experiments in monolayer MoS 2 , MoSe 2 , WS 2 , and WSe 2 confirmed the existence of excitonic states that are localized in the band gap [16][17][18][19][20] . Furthermore, a few theoretical works pertinent to the excitonic absorption spectrum of these materials have appeared recently [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%